Newly crosslinked chitosan- and chitosan-pectin-based hydrogels with high antioxidant and potential anticancer activity. (15th August 2022) - Dziadek, Michal; Dziadek, Kinga; Salagierski, Szymon; Drozdowska, Mariola; Serafim, Andrada; Stancu, Izabela-Cristina; Szatkowski, Piotr; Kopec, Aneta; Rajzer, Izabella; Douglas, Timothy E.L.; Cholewa-Kowalska, Katarzyna
Abstract: Monoaldehydes, due to natural origin and therapeutic activity, have attracted great attention for their ability to crosslink chitosan hydrogels for biomedical applications. However, most studies have focused on single-component hydrogels. In this work, chitosan-based hydrogels, crosslinked for the first time with 2, 3, 4-trihydroxybenzaldehyde (THBA), were modified with pectin (PC), bioactive glass (BG), and rosmarinic acid (RA). All of these were not only involved in the crosslinking, but also modulated properties or imparted completely new ones. THBA functioned as a crosslinker, resulting in improved mechanical properties, high swelling capacity and delayed degradation and also imparted high antioxidant activity and antiproliferative effect on cancer cells without cytotoxicity for normal cells. Hydrogels containing PC showed enhanced mechanical strength, while the combination with BG gave improved stability in PBS. All hydrogels modified with BG exhibited the ability to mineralise in SBF. The addition of RA enhanced antioxidant and anticancer activities and promoting the mineralisation process.